The End as Enjambment: Critical Inquiries Beyond the End… - Sebastian Huber (Current Objectives of Postgraduate American Studies, 2015)
This introduction investigates the proliferation of ends in late 20th century and early 21st century fiction, theory, and culture. By investigating some characteristics of ‘ends’ I reflect upon some of the aporias of the concept of the end. I conclude by analyzing Colson Whitehead’s Zone One “(2013) for its discussion of the end of the world and the end of race and show that the novel conceives of a critical form of post-apocalypticism in a racialized context.